Estrategia de marketing del Gimnasio “Rage Gym” en la parroquia Barreiro del cantón de Babahoyo, periodo 2022. - León Guaranda, Ariel Medardo (2023)
The scientific research carried out evaluated the marketing strategy of the "Rage Gym" gym in the Barreiro parish of the canton of Babahoyo during the period 2022. A mixed methodology was used that combines qualitative and quantitative techniques, as well as a descriptive investigation with a sample of users. of the gym and an interview with the owner of the training room. The result found indicates that the lack of an effective customer loyalty strategy may be one of the reasons why the company has experienced a decrease in the number of customers in recent months. In addition, the company must improve its online marketing and advertising strategy and ensure that the implementation of new technologies is effective. Therefore, it is recommended to implement an effective customer loyalty strategy that includes rewards programs, special offers, and discounts for loyal customers. It is also recommended to carry out a regular evaluation of advertising and marketing campaigns, consider hiring an online advertising and marketing expert, and ensure that the implementation of new technologies is effective in maintaining and increasing your customer base in the local market. and compete with other gyms in the area.